Relationship between Communication Competence and Psychological Well-being of Flood Victims in Malaysia - Mustaffa, Che Su; Marzuki, Najib Ahmad; Rahaman, Nur Haffiza (International Review of Management and Marketing, 2016)
The purpose of this paper is to examine the relationship between psychological weel being and communication competence among flood reliefs workers as perceived by disaster victim underlying the recent interest on communication studies and disaster management, discusses the current issues and offers a future research perspective. It offers to understand communication competence of relief workers in the areas of communication studies in Malaysian organizations and how does this concept relate to psychological well being of flood victim. The cross-sectional data for this study were collected via a survey of 270 flood victims. The study highlights the important of flood relief workers' communication competence from different aspect as perceived by the flood victim. The result indicate that there is a relationship between both variables. In sum, this study provides theoretical contributions to communication competence research and the literature on communication studies. The paper draws attention to the current issues of the disaster management on communication studies and highlights it for future directions. Keywords: Psychological well-being, communication competence, flood victim JEL Classifications: Q54